Randomized, Double-Blind, Placebo-Controlled Trial of a Throat Spray with Selected Lactobacilli in COVID-19 Outpatients - Ilke De Boeck; Eline Cauwenberghs; Irina Spacova; Thies Gehrmann; Tom Eilers; Lize Delanghe; Stijn Wittouck; Peter A. Bron; Tim Henkens; Imane Gamgami; Alix Simons; Ingmar Claes; et al. (Microbiology Spectrum, 2022)
ABSTRACT Primary care urgently needs treatments for coronavirus disease 2019 (COVID-19) patients because current options are limited, while these patients who do not require hospitalization encompass more than 90% of the people infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here, we evaluated a throat spray containing three Lactobacillaceae strains with broad antiviral properties in a randomized, double-blind, placebo-controlled trial. Before the availability of vaccines, 78 eligible COVID-19 patients were randomized to verum (n = 41) and placebo (n = 37) within 96 h of a positive PCR-based SARS-CoV-2 diagnosis, and a per-protocol analysis was performed. Symptoms and severity were reported daily via an online diary. Combined nose-throat swabs and dried blood spots were collected at regular time points in the study for microbiome, viral load, and antibody analyses. The daily reported symptoms were highly variable, with no added benefit for symptom resolution in the verum group. However, based on 16S V4 amplicon sequencing, the acute symptom score (fever, diarrhea, chills, and muscle pain) was significantly negatively associated with the relative abundance of amplicon sequence variants (ASVs) that included the applied lactobacilli (P < 0.05). Furthermore, specific monitoring of these applied lactobacilli strains showed that they were detectable via quantitative PCR (qPCR) analysis in 82% of the patients in the verum group. At the end of the trial, a trend toward lower test positivity for SARS-CoV-2 was observed for the verum group (2/30; 6.7% positive) than for the placebo group (7/27; 26% positive) (P = 0.07). These data indicate that the throat spray with selected antiviral lactobacilli could have the potential to reduce nasopharyngeal viral loads and acute symptoms but should be applied earlier in the viral infection process and substantiated in larger trials. IMPORTANCE Viral respiratory tract infections result in significant health and economic burdens, as highlighted by the COVID-19 pandemic. Primary care patients represent 90% of those infected with SARS-CoV-2, yet their treatment options are limited to analgesics and antiphlogistics, and few broadly acting antiviral strategies are available. Microbiome or probiotic therapy is a promising emerging treatment option because it is based on the multifactorial action of beneficial bacteria against respiratory viral disease. In this study, an innovative topical throat spray with select beneficial lactobacilli was administered to primary COVID-19 patients. A remote study setup (reducing the burden on hospitals and general practitioners) was successfully implemented using online questionnaires and longitudinal self-sampling. Our results point toward the potential mechanisms of action associated with spray administration at the levels of viral loads and microbiome modulation in the upper respiratory tract and pave the way for future clinical applications of beneficial bacteria against viral diseases.